Chubby mothers-maternal and perinatal outcome in high body mass index - Garikapati, Kavitha; Gayathri, K. B.; Lalitha, K. Naga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Obesity is a state of excess adipose tissue mass. Body mass index (BMI) is a crucial predictor of nutritional status of pregnant women. High BMI may lead to various adverse maternal and perinatal outcomes. This study is designed to see the effect of maternal BMI on pregnancy outcome and perinatal outcome according to Asian standards. Methods: This is an institutional retrospective, descriptive study of 100 pregnant women conducted in the department of obstetrics and gynaecology of a rural tertiary centre Dr. PSIMS and RF, Chinaoutpalli, Gannavaram, Vijayawada, AP, India from June 2017 to July 2019. Results: It was observed that as BMI increased risk of complications increased like hypertension disorders in pregnancy, gestational diabetes mellitus, preterm labour. Also risk of macrosomia, operative delivery, Neonatal intensive care unit (NICU) admissions increased. Conclusions: As maternal BMI is a good predictor has strong correlation with pregnancy complications and outcomes, measures should be taken to motivate for pre pregnancy counselling regarding weight management and close surveillance in antenatal period to diagnose at the earliest any complications.